Destination Image Dimension: A Descriptive Analysis of Foreign Visitors At Borobudur, Indonesia - Herlan Suherlan; Nurdin Hidayah (Journal of Indonesian Tourism and Development Studies, 2021)
This study aims to determine the dominant factors forming the image in the context of tourism destinations. The quantitative method with the survey format chosen in this study, where the data obtained through convenience sampling were analyzed using Principal Component Analysis (PCA). The results showed that the image of Borobudur as a destination was formed by 4 dominant factors, namely: Core Attractions, Supporting Attractions, Services, and Experience. The results of this study have implications for destination marketers to get a clear picture of how the image is in the eyes of tourists so that programs or activities for developing and improving the quality of a destination are more focused and right on target. This paper fills a gap in the generic branding literature by adopting an empirical stance in describing image-forming factors in the context of tourism destinations.Keywords: Brand image, destination branding, destination image, tourism destinations.